What Drives Female Fertility in the Philippines? Evidence from 50 Years of National Demographic and Health Surveys - Michael Ralph M. Abrigo; Katha Ma-i M. Estopace (Philippine Institute for Development Studies (PIDS), 2023)
We trace the drivers of the Philippines' fertility decline over the last fifty years culminating in 2022 with a below-replacement 1.9 total fertility rate. Applying a modified Kitagawa-OaxacaBlinder decomposition on the combined experiences of about 65,000 married women in six rounds of the Philippine National Demographic (and Health) Survey, we show that the most effective contraceptives may not necessarily be delaying marriage or raising modern contraceptive use. Our analyses indicate that the greatest driver of fertility decline over the last half century in the Philippines is improving material measures of well-being, with marriage and contraceptive use playing only secondary roles. While raising female fertility in the future may be a possibility, this will not likely go significantly above replacement levels. Population ageing is an imminent reality for the Philippines.
Keywords: 330; fertility; population; decomposition; Philippines